2017
DOI: 10.7202/1040403ar
|View full text |Cite
|
Sign up to set email alerts
|

Individuals’ Assessment of Corporate Social Performance, Person-Organization Values and Goals Fit, Job Satisfaction and Turnover Intentions

Abstract: Recent research in the domain of corporate social responsibility (CSR) has underlined the importance of moving away from an institutional perspective of CSR towards research at the micro-level. Such calls have insisted on the necessity of a developing a deeper, and more nuanced understanding of its impacts and mechanisms at the individual level. This paper addresses this issue by focusing on the nexus between how employees judge their companies’ actual CSR performance and how that judgement can affect individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…(Valentine, & Godkin 2017) Perceived CSR was related to increased employees' fit with and commitment to their employer and lead to lower turnover intentions. (Hudson et al, 2017) Employee assessments of CSP are positively attached to perceived P-O fit.…”
Section: Csr and P-o Fitmentioning
confidence: 99%
“…(Valentine, & Godkin 2017) Perceived CSR was related to increased employees' fit with and commitment to their employer and lead to lower turnover intentions. (Hudson et al, 2017) Employee assessments of CSP are positively attached to perceived P-O fit.…”
Section: Csr and P-o Fitmentioning
confidence: 99%
“…Turker (2009a) also found a positive relationship between organisational commitment and aspects of external-CSR (customers, social and nonsocial stakeholders) and internal-CSR (employees) but failed to find a significant impact from another aspect of external-CSR (government). In a recent study, Hudson et al (2017) found that perceived CSR had a positive relationship with person-organisation fit and that such congruence was a significant factor in mediating the relationship between CSR and turnover intention.…”
Section: Role Of Csr In Moderating the Psm And Organisational Commitment Relationshipmentioning
confidence: 99%
“…Early CSR literature explored macro-level instrumental outcomes such as organisational financial and competitive performance. However, over the past two decades there has been a growing focus on CSR at the micro-level and the normative impact it has on employee attitudes and behaviour (Hudson et al, 2017). Micro-CSR can be defined as "the study of the effects and experiences of CSR (however it is defined) on individuals (in any stakeholder group) as examined at the individual level of analysis" (Rupp and Mallory, 2015;p.216).…”
Section: Role Of Csr In Moderating the Psm And Organisational Commitment Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Management culture, as an integral part of organisational culture, albeit indirectly, is often mentioned in works by different authors describing the criteria of organisational culture. Tichomirova [1] points out strong relationships between workers of the organisation, Zohar and Marshall [2] distinguish significance of general reasoning and other authors [3][4][5][6][7][8][9] highlight the principles of ideology, beliefs and values shared by all enterprises. However, substantially high level of management culture is essential for successful implementation of corporate social responsibility [10].…”
Section: Introductionmentioning
confidence: 99%